2020
DOI: 10.3390/polym12092100
|View full text |Cite
|
Sign up to set email alerts
|

Causes of the Gloss Transition Defect on High-Gloss Injection-Molded Surfaces

Abstract: The gloss transition defect of injection-molded surfaces should be mitigated because it creates a poor impression of product quality. Conventional approaches for the suppression of the gloss transition defect employ a trial-and-error approach and additional equipment. The causes of the generation of a low-gloss polymer surface and the surface change during the molding process have not been systematically analyzed. This article proposes the causes of the generation of a low-gloss polymer surface and the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The packing pressure and time of the packing stage were expected to be the most influential factors on the part weight because the packing stage compensates for shrinkage of the polymer material. However, the injection speed was expected to be less influential than the packing pressure and time because the filling stage predominantly affects the surface quality, not shrinkage in the packing and cooling stages [ 34 ]. These are common process parameters that are tuned to optimize the injection-molding process.…”
Section: Methodsmentioning
confidence: 99%
“…The packing pressure and time of the packing stage were expected to be the most influential factors on the part weight because the packing stage compensates for shrinkage of the polymer material. However, the injection speed was expected to be less influential than the packing pressure and time because the filling stage predominantly affects the surface quality, not shrinkage in the packing and cooling stages [ 34 ]. These are common process parameters that are tuned to optimize the injection-molding process.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between the cooling times used did not cause a visible difference in the filling. Gim et al also concluded the fact that the higher injection speed could add more melt into the microstructures before the maximum cavity pressure was reached [ 9 ]. This was due to an increased injection rate, leading to a decrease in melt viscosity that improves the melt flow in microstructures.…”
Section: Methodsmentioning
confidence: 99%
“…The replication quality of molded parts or even their mechanical properties can be improved by optimizing process parameters and controlling material flow. Therefore, an optimization approach has been used to improve the mechanical properties of the molded part made by polypropylene (PP) [ 4 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be also used to minimize the reduction in tensile strength in parts, where weld lines are present [ 21 , 22 , 23 ]. Besides, the high cavity surface temperature is commonly used to improve surface quality (removal of weld lines’ presence, obtaining high-gloss surface, better replication of microstructure of the cavity surface) [ 6 , 11 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%